University Bookstores and the Promotion of Reading - Georgina Araceli Torres Vargas (Universidad Nacional Autónoma de México, Instituto de Investigaciones Bibliográficas, 2021)
The university press production derives from research, teaching and dissemination activities undertaken at its campuses. This generates an offer of highly specialized editions, which results in a small number of potential readers, almost all researchers, professors and students from the university itself. The low consumption of university publishing production is also due to a limited distribution and sale through conventional channels, which prevents reaching other audiences. This text shows some alternatives that can be adopted by university bookstores in order to promote the reading of their publications.